PENGAWASAN HUKUM TERHADAP PERBUATAN PENYALAHGUNAAN WEWENANG ( DETOURNEMENT DE POUVIOR ) OLEH PEJABAT DI LINGKUNGAN PEMERINTAH KOTA SAMARINDA - Mohammad Saifullah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe process of achieving a country with good government requires a tool in bringing the component policies or government regulations for the realization of national goals. The administration tool is a responsible government in this case the Civil Servants (PNS) and is now called the State Civil Apparatus (ASN) as stipulated in Law No. 5 of 2014. The establishment of discipline, ethics and moral decision-making level officials, it is necessary to counteract measures taken full nuances of personal interests and groups / group. If that happens, without realizing that it is an abuse of authority of office. Embodiment abuses of authority of office mostly affects the occurrence of corruption, collusion, nepotism (KKN). Abuse of office or power is as one of the important elements of corruption are regulated in Law Number 31 of 1999 junto Act No. 20 of 2001 on Corruption Eradication. A critical element is meant abuse of authority, which may cause financial loss or the State's economy. Abuse of power or authority, especially in the management and designation of state finances by the state apparatus, in fact it was an act of corruptiion because of its detrimental to the country's economy and state finances.